Integrated nutrient management for sustaining productivity and fertility under rice (Oryza sativa)-based cropping system - MONDAL, S S; CHETTRI, M (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1991-93 to study the integrated nutrient management for high productivityand fertility building under rice (Olyza sativa L.)-based cropping system with special reference to sulphurthrough ammonium sulphate along with green manure in situ and farmyard manure to rice only. The results showedthat maximum yield of rice (4.96 and 5.77 tonnes/ha in wet and dry season, respectively) was obtained in rainy seasonrice (Oryza sativa L.) - oat (Avena sativa L.) as fodder-winter season rice-cowpea (Vigna unguiculate (L.) Walp.) asgreen manure and rainy season rice-rice hean (Vigna umbellata Thumb.) as green manure winter-season rice-sorghum(Sorghum bicolar (L.) Moench) as fodder sequence where rainy and winter season rice were green manured withcowpea and rice-bean in addition to 50% of the recommended dose of NPK through urea, diammonium phosphate andmuriate of potash (60, 17.6, 33.2 and SO, 26.4, 49.8 kg NPK/ha in rainy and winter season rice, respectively) + farmyardmanure 10 tonnes/ha to rice only, which also gave maximum fodder or green matter yield of succeeding crop.With this fertilizer management treatment higher net return, net production value (2.92), agronomic efflcacy, physiologicalefficiency and recovery fraction (RF) were recorded in the sequence where both rainy and winter season ricewere grown after cowpea and rice bean as fodder. The uptake of nutrients (N,P,Kand S) by the crops in sequence andnutrient status of soil were also improved where green manuring was done before transplanting rice with same fertilizermanagement treatment (50% NPK + farmyard manure 10 tonnes/ha).